Strategi Humas Kemendikbudristek dalam Menyosialisasikan Kebijakan Merdeka Belajar kepada Sidina Community - Syifa Albalqis Danayomi; Christina Tri Hendriyani (Universitas Sebelas Maret (UNS), 2024)
The Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) is the ministry responsible for the education sector in Indonesia. During Nadiem Makarim's tenure, Kemendikbudristek introduced a new policy in the field of education called the